2006
DOI: 10.1681/asn.2006020118
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease in Long-Term Survivors of Hematopoietic Cell Transplantation

Abstract: High-dose myeloablative hematopoietic cell transplantation is becoming an increasingly common treatment modality for a variety of diseases. Patient survival may be limited by substantial treatment-related toxicities, including chronic kidney disease (CKD). Although the majority of CKD after transplantation is idiopathic, thrombotic microangiopathic syndromes and nephrotic syndrome have been described. Epidemiology, pathogenesis, and potential treatment options for the various clinical syndromes that are associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
112
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 84 publications
1
112
0
2
Order By: Relevance
“…[1][2][3] In the acute setting, renal failure may be due to renal toxicity of medications (chemotherapeutic, antibiotic, or immunosuppressive), tumor lysis syndrome, renal ischemia (including hypovolemia, veno-occlusive disease, etc), sepsis, infection (bacterial, fungal, or viral), or effects of radiation. [4][5][6] A hemolytic-uremia-like syndrome, often referred to as bone marrow transplant nephropathy, may manifest later (3-6 months or post-transplantation later), and classically shows histopathologic features of thrombotic microangiopathy with endothelial injury. [4][5][6][7] Although exposure of kidneys to radiation during hematopoietic cell transplantation has been hypothesized as a risk factor for bone marrow transplant nephropathy, studies have shown conflicting data regarding renal shielding and long-term renal insufficiency.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] In the acute setting, renal failure may be due to renal toxicity of medications (chemotherapeutic, antibiotic, or immunosuppressive), tumor lysis syndrome, renal ischemia (including hypovolemia, veno-occlusive disease, etc), sepsis, infection (bacterial, fungal, or viral), or effects of radiation. [4][5][6] A hemolytic-uremia-like syndrome, often referred to as bone marrow transplant nephropathy, may manifest later (3-6 months or post-transplantation later), and classically shows histopathologic features of thrombotic microangiopathy with endothelial injury. [4][5][6][7] Although exposure of kidneys to radiation during hematopoietic cell transplantation has been hypothesized as a risk factor for bone marrow transplant nephropathy, studies have shown conflicting data regarding renal shielding and long-term renal insufficiency.…”
mentioning
confidence: 99%
“…[4][5][6] A hemolytic-uremia-like syndrome, often referred to as bone marrow transplant nephropathy, may manifest later (3-6 months or post-transplantation later), and classically shows histopathologic features of thrombotic microangiopathy with endothelial injury. [4][5][6][7] Although exposure of kidneys to radiation during hematopoietic cell transplantation has been hypothesized as a risk factor for bone marrow transplant nephropathy, studies have shown conflicting data regarding renal shielding and long-term renal insufficiency. 5,[8][9][10][11][12] Other causes of thrombotic microangiopathy must be considered in hematopoietic cell transplant recipients, including exacerbation of endothelial injury by chemotherapy, immune-mediated injury, and perhaps most notably, cyclosporine inhibitor toxicity, given as prophylaxis or treatment for graft-versus-host disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transplanted patients experience various kidney diseases throughout the clinical course following HSCT [1,2]. Among them, acute kidney injury (AKI) develops in the early phase of HSCT and represents one of the most critical complications, as it largely governs the fate of the patients [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…1 Renal disease is a major complication post-HCT with acute kidney injury (AKI) and chronic kidney disease (CKD) significantly contributing to nonrelapse mortality in these patients. 2,3 The genesis of renal disease after myeloablative allogeneic HCT is multifactorial and the identification of risk factors for both AKI and CKD is critical to allow for preventive measures. We have identified previously several risk factors including sinusoidal obstruction syndrome (SOS), amphotericin use and baseline serum creatinine.…”
Section: Introductionmentioning
confidence: 99%